Analysis of Rhetorical Structures in Writing Introduction Section of Research Articles by Native English - Ramadhanty, Nadya (Journal of English for Specific Purposes in Indonesia, 2025)
This research was purposely conducted to describe the Rhetorical Structures of Native English in the writing introduction section of research articles. The data was chosen from the research article published by two disciplines of journal which is Journal of Pragmatics(JOP) and Journal of English for Academic Purposes (JEAP). This present study was conducted to find out whether the introduction section of the selected introduction in both journals follows the fundamental CARS Model by Swales (2004). Ten introductions of research articles from both journals were annotated in this research. Five research publications were deliberately selected from each discipline. The findings indicate that the introduction sections of research articles from two journal disciplines authored by native English speakers predominantly encompass the moves and steps outlined in Swales' (2004) CARS model, with Move 1 and Move 3 regarded as a mandatory move. Meanwhile, Move 2 is regarded as arbitrary. In conclusion, it can be inferred that the utilization of rhetorical patterns is not contingent upon the authors' proficiency in written language; rather, authors must implement rhetorical realizations in composing their introductions.